2019
DOI: 10.1167/iovs.18-26077
|View full text |Cite
|
Sign up to set email alerts
|

Actin Dynamics, Regulated by RhoA-LIMK-Cofilin Signaling, Mediates Rod Photoreceptor Axonal Retraction After Retinal Injury

Abstract: Purpose Retraction of the axon terminals of rod photoreceptors after retinal detachment breaks the first synapse in the visual pathway, resulting in visual impairment. Previous work showed that the mechanism of axonal retraction involves RhoA signaling and its downstream effector LIM Kinase (LIMK) activation. We examined the response of the downstream component cofilin, a direct binding protein of actin filaments, as well as the regulation by RhoA-LIMK-Cofilin signaling of actin assembly/disassemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…2,3,17,20 Such remodeling events are not unique for RP, because they have also been reported in other genetic 3 and environmental diseases such as AMD 22 and the aging retina, 39 as well as retinal detachment. 21,23 However, there is a considerable heterogeneity in the progression of neuronal morphologic changes and network rewiring in retinal dystrophies, owing to the diverse molecular pathways underlying the retinal cell dysfunction. In this study, we examined the disease-associated remodeling of axonal and dendritic processes in the outer retina of affected dogs carrying the XLPRA1 mutation in the RPGR gene.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2,3,17,20 Such remodeling events are not unique for RP, because they have also been reported in other genetic 3 and environmental diseases such as AMD 22 and the aging retina, 39 as well as retinal detachment. 21,23 However, there is a considerable heterogeneity in the progression of neuronal morphologic changes and network rewiring in retinal dystrophies, owing to the diverse molecular pathways underlying the retinal cell dysfunction. In this study, we examined the disease-associated remodeling of axonal and dendritic processes in the outer retina of affected dogs carrying the XLPRA1 mutation in the RPGR gene.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies showed that activation of RHOA GTPase, a key regulator of the cytoskeleton, and its downstream signaling effectors mediate rod axonal retraction after retinal detachment and injury. 21,23 We hypothesized that disease-associated perturbations in axon guidance signaling pathways, known to regulate the activity of RHO GTPases, underlie or contribute to rod axon retraction and degeneration. Two evolutionary conserved axon guidance receptors ROBO1 and ROBO2 that mediate repulsion in response to binding of SLIT ligands during neuronal development 25,27,28,41 were tested in this study for possible association between their expression pattern and synaptic remodeling in XLPRA1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rho-GTPase is known to be involved in the activation of cofilin and the promotion of actin cytoskeletal organization. 32,33 The data showed that toxin-B, an inhibitor of Rho-GTPase, blocked LPA-mediated prevention of radiation effects on cofilin and F-actin organization ( Figure 1D). To confirm the effects of radiation on the tight junction, we examined the effects of radiation and LPA in I-mC C12 cell monolayers, a non-transformed mouse intestinal epithelial cell line with rich in LPA2 receptors.…”
Section: Lpa Attenuates Radiation-induced Disruption Of Tight Junctmentioning
confidence: 95%